2010
DOI: 10.1021/ja910445r
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Reduction of CO2 to CO Mediated by an Anionic Niobium Nitride Complex

Abstract: The terminal nitride anion complex [Na][N[triple bond]Nb(N[(t)Bu]Ar)(3)] ([Na][1], Ar = 3,5-Me(2)C(6)H(3)) reacts quantitatively with CO(2) to give the carbamate complex [Na][O(2)CN[triple bond]Nb(N[(t)Bu]Ar)(3)] ([Na][O(2)C-1]). The structure of [Na][O(2)C-1] as the bis-12-crown-4 solvate, as determined by X-ray crystallography, displays a unique N-bound carbamate ligand without any metal-oxygen interactions. When treated with organic acid anhydrides or acid chlorides, complex [Na][O(2)C-1] reacts via salt el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 27 publications
4
92
0
1
Order By: Relevance
“…The most stable structure of 1-Nb has a C 3 point group. As seen from Figure 21 The free-energy barrier for the formation of 2-Nb from 1-Nb + CO 2 is calculated to be 6.2 kcal/mol, indicating that 1-Nb easily traps CO 2 .…”
Section: ■ Computational Detailsmentioning
confidence: 91%
See 3 more Smart Citations
“…The most stable structure of 1-Nb has a C 3 point group. As seen from Figure 21 The free-energy barrier for the formation of 2-Nb from 1-Nb + CO 2 is calculated to be 6.2 kcal/mol, indicating that 1-Nb easily traps CO 2 .…”
Section: ■ Computational Detailsmentioning
confidence: 91%
“…30 In the CPCM calculations, THF was used as the solvent, corresponding to the experimental conditions. 21 In this paper, solvation-corrected relative free energies are used to analyze the reaction pathways calculated. Wiberg bond indices (WBI) were obtained by natural bond orbital (NBO) analysis.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table S4, it can be found that both the lengths of C3AO1 bond and C3AO2 bond increase in TS2 compared with those in the free carbon dioxide. Referring to the increase in the length of CAO bond is used to measure the activation of carbon dioxide [28][29][30][31][32]. Besides, the lengths of NAC3 bond and O1AC1 bond shorten from 3.030 Å, 3.909 Å in compound 2 to 1.709 Å, 2.365 Å in TS2, respectively.…”
Section: The Reaction Mechanism With No Catalyst (Path I)mentioning
confidence: 99%